GST good way to get revenue - Shah, Ahmad Syazwan (New Sunday Times, 2013)
PRIME Minister Datuk Seri Najib Razak has tabled a budget to address the people's needs and reduce the budget deficit, with incentives to generate economic activities to increase revenue.The government has allocated a substantial amount to upgrade facilities in Sabah and Sarawak,which shows the government is not focusing on the peninsula.